The effect of feedstock densification on the process and product properties of sugarcane leaves pyrolysis - Adi Setiawan; Ananda Fringki; M. Iqbal Hifzi; Shafira Riskina; Jalaluddin; Eddy Kurniawan; Burhanuddin (AIMS Environmental Science)
Sugarcane leaves are the main residue constitute approximately 14% of the total weight of the remaining sugarcane after harvesting. An effective method for processing sugarcane leaves residues is needed at low cost without causing any environmental problem. This research aims to disclose the effect of sugarcane leaves densification method applied prior to pyrolysis process in a pilot scale reactor. To evaluate the process and its product, the experiments were carried out into two types: (i) pyrolysis of sugarcane leaves without densification at 320 ℃ with a variation of pyrolysis time for 100,120, and 130 minutes and (ii) pyrolysis of densified sugarcane leaves with the variation of pyrolysis temperature 320 ℃ and 420 ℃. The investigated conditions showed that the effect of sugarcane leaves densification prolong the pyrolysis time up to 240 minutes at a pyrolysis temperature of 320 ℃, and increased the yield of biochar and bio-oil products up to 41% and 38%, respectively. However, in term of the physical properties of biochar products, the fixed carbon content decreased by 7% when the sugarcane leaves were compacted. While other parameters found no significant difference in pyrolysis at 320 ℃, the effect of sugarcane leaves densification is very beneficial especially when the pyrolysis was performed at 420 ℃.